The Concept of Criminalization of Judicial Negligence: The Merit System and Decision Evaluation as Judicial Reform - Robert Febriyanto Turnip; Maman Budiman (Interdisciplinary Social Studies, 2025)
The failure of the supervision system and sanctioning mechanisms to address the negligence of judges has created an urgent need to reform the justice system. Disparities in the independence and accountability of judges create accountability gaps in the justice system. This study uses a juridical-normative approach to analyze positive legal norms, legal principles, and the systematics of laws and regulations related to the accountability of judges for negligence in deciding criminal cases. This study reconceptualizes culpa lata into two categories: negligence that leads to KKN, using the Theory of Rational Choice, Theory of Opportunity, and the Theory of White Collar Crime based on motives and manipulation attempts. Non-KKN Negligence, in the first phase, examines the individual level based on Social Control Theory. The second phase analyzes the failure of the supervisory system to function at the institutional level using the Theory of Sociological Institutionalism and the Theory of Rational Choice Institutionalism. The findings suggest that criminalizing culpa lata is a last resort. Therefore, the authors propose an integrated concept consisting of three components: the evaluation of AI-based judgments synergized with the merit system as a tool for detecting negligence, the special court as the final judicial forum, and the criminalization of culpa lata as a sanction mechanism. This concept aims to balance judicial independence with accountability through effective and organized mechanisms in order to restore public trust and realize the role of the Supreme Court in Indonesia.